Two Antibiotics, Ampicillin and Tetracycline, Exert Different Effects in HT-29 Colorectal Adenocarcinoma Cells in Terms of Cell Viability and Migration Capacity. - Hut, Emil-Florin; Radulescu, Matilda; Pilut, Nicolae; Macasoi, Ioana; Berceanu, Delia; Coricovac, Dorina; Pinzaru, Iulia; Cretu, Octavian; Dehelean, Cristina (Current Oncology, 2021)
Antibiotics are considered the cornerstone of modern medicine; however, currently, antibiotic resistance has become a global health issue. Antibiotics also find new uses in the treatment of other pathologies as well as cancer. The present study aimed to verify the impact of tetracycline and ampicillin in a colorectal adenocarcinoma cell line, HT-29. The effects of the two antibiotics on cell viability and nucleus were evaluated by the means of MTT assay and the Hoechst staining method, respectively. The irritant potential at vascular level of the chorioallantoic membrane was tested by the HET-CAM assay. Treatment of HT-29 cells with the two antibiotics determined different effects: (i) tetracycline induced a dose- and time-dependent cytotoxic effect characterized by decreased cell viability, changes in cells morphology, apoptotic features (nuclear fragmentation), and inhibition of cellular migration, whereas (ii) ampicillin exerted a biphasic response--cytotoxic at low doses and proliferative at high concentrations. In terms of effect on blood vessels, both antibiotics exerted a mild irritant effect. These results are promising and could be considered as starting point for further in vitro studies to define the molecular mechanisms involved in the cytotoxic/proliferative effects.